Challenges of green consumption in China: a household energy use perspective. Issue 2 (2nd April 2016) - Zhang, Haiyan; Lahr, Michael L.; Bi, Jun
ABSTRACT: To encourage economic progress, China's government has been pushing domestic consumption as a substitute for its waning growth in investment and exports. It has also been promoting greener policies for growth, of which green consumerism is a prime component. By examining the economy through the lens of household energy consumption, this paper lays out the challenges the nation must overcome through green consumption. We explore the trends in household energy use and decompose energy used indirectly by households into six factors: changes in total population, urbanization rate, energy efficiency, interindustry input mix, household consumption preferences, and per capita household consumption level. Doing so yields insights into how progress in industrial technology, household income, urbanization, and lifestyles has affected energy use in the production of goods and services used by households. It also offers policy suggestions on how China might guide lifestyle changes to effect green consumption.